Evaluation of organotin (IV) dithiocarbamate compounds as potential anti-leukemia agents towards CCRF-CEM (CCL-119) cell line: Cytotoxic, apoptotic, cell cycle and genotoxic study - Nabiha Hidayah Abdul Razak; Nur Rasyiqin Rasli; Norsyahira Mohamad Zamri; Asmah Hamid; Normah Awang; Nurul Farahana Kamaludin (PLoS ONE, 2025)
Acute lymphoblastic leukemia (ALL) is a common cancer affecting children worldwide, and current treatment has adverse effects such as neurotoxicity. To overcome this problem, new organotin (IV) dithiocarbamate compounds were synthesized. In this study, the T-lymphoblastic leukemia cell line (CCL-119) was tested against seven new compounds: diphenyltin (IV) diisopropyl dithiocarbamate (ODTC 1), diphenyltin (IV) diallyl dithiocarbamate (ODTC 2), triphenyltin (IV) diisopropyl dithiocarbamate (ODTC 3), triphenyltin (IV) diallyl dithiocarbamate (ODTC 4), triphenyltin (IV) diethyl dithiocarbamate (ODTC 5), dimethyltin (IV) diisopropyl dithiocarbamate (ODTC 6) and dimethyltin (IV) diethyl dithiocarbamate (ODTC 7) hereafter referred to as ODTC 1–7, to identify their cytotoxic effects (MTT assay), mode of cell death (Annexin V FITC/PI staining) and effects on the cell cycle (RNase/PI staining) as well as genotoxic effects (alkaline comet assay). Results obtained after 24 hours of exposure showed that all organotin (IV) dithiocarbamate compounds (ODTC 1–7) exhibited potent cytotoxicity, with median inhibitory concentration (IC50) values ranging from 0.18 µM to 3.10 µM. The selectivity index showed that diphenyltin (IV) and triphenyltin (IV) dithiocarbamate compounds are more selective towards CCL-119 cells. All ODTC compounds induced apoptosis in CCL-119 cells, and each compound caused cell cycle arrest at specific phases, indicating diverse mechanisms of action. Apoptosis and cell cycle arrest were confirmed by flow cytometry. Treatment of the compounds caused significant (p < 0.05) DNA damage compared to the negative control, with ODTC 1 causing the highest genotoxic effects. In conclusion, diphenyltin (IV) and triphenyltin (IV) dithiocarbamate compounds show good potential as anti-leukemia agents. However, further studies on the mechanisms of action need to be conducted to have better insights into the effect of this compound on CCL-119 leukemia cells.